An analysis of MASW responses for urban ground subsidence. Issue 1 (1st December 2016) - Kim, Bitnarae; Nam, Myung Jin; Kim, Dongwoo; Jang, Hannuree; Song, Seo Young
Abstract : Ground subsidence occurred by sink-hole and cavities in the city has become a serious problem in Korea so these days geophysics survey study for the near-surface become active. Multichannel analysis of surface waves (MASW) is useful survey method to detect anomaly under the subsurface and characterize the structure of S wave velocity of the medium. In this study, we set subsurface seismic model with reference to the real coring data near the sink-hole outbreak point. To define elastic properties of the medium from the core data, we apply ground physics model (GPM) and use Gassman's equation, the typical model for GPM. For Gassman's equation input, we consider and assume rock properties as porosity and bulk modulus and so on. The algorithm for this study is time-domain 2D FDM elastic wave modelling algorithm which is based on staggered grid and it damp the reflected wave in the convolutional perfectly matched layer (CPML) zone. We carry out synthetic modelling experiments with the composited medium model and analyse the sensitivity of the underground cavity effect. To set variables of the cavity, we adjust the scale and the depth of the cavity. MASW modelling results show the effect of the cavity and we will study further for the synthetic experiments.